Characterization of the antibody response to vaccination and or infection with porcine circovirus type 2 and identification and characterization of a decoy epitope in the capsid protein - Trible, Benjamin Ralph (Kansas State University, 2021)
Chapter 1: Porcine circovirus-associated disease (PCVAD) encompasses a group of complex, multi-factorial syndromes, which are dependent on infection with porcine circovirus type 2 (PCV2). Current strains of PCV2 circulating in the field are phylogenically classified into two groups, termed PCV2a and 2b. Outbreaks of severe PCVAD in North America in 2005 are linked with a shift in the predominant circulating genotype, from PCV2a to PCV2b. Therefore genotype specific differences in pathogenesis and antigenicity have been suggested. Overall, evidence suggests pathogenicity is a function of the specific PCV2 isolate, regardless of genotype. In addition, only minor antigenic differences have been reported. In terms of immunopathogenisis, a genotypically conserved immune decoy epitope, located in the C-terminal region of the capsid protein, provides an explanation for the inability to identify pathogenic differences between genotypes. Finally, genetic variation of PCV2 and the resulting consequences with respect to vaccination and diagnostics is discussed. Chapter 2: Open reading frame 2 (ORF2) of porcine circovirus type 2 (PCV2) codes for the 233 amino acid capsid protein (CP). Baculovirus-based vaccines that express only ORF2 are protective against clinical disease following experimental challenge or natural infection. The goal of this study was to identify regions in CP preferentially recognized by sera from experimentally infected and vaccinated pigs, and compare these responses to pigs diagnosed with porcine circovirus-associated disease (PCVAD), including porcine multi-systemic wasting syndrome (PMWS) and porcine dermatitis and nephropathy syndrome (PDNS). The approach was to react porcine sera with CP polypeptide fragments followed by finer mapping studies using overlapping oligopeptides that covered amino acids 141-200. The results showed that vaccinated pigs preferentially recognized only the largest CP(43-233) polypeptide fragment. A subset of experimentally infected pigs and pigs with PDNS showed strong reactivity against a CP oligopeptide, 169-STIDYFQPNNKR-180. Alanine scanning identified Y-173, F-174, Q-175 and K-179 as important for antibody recognition. The results from this study support the notion of PCV2 modulation of immunity, including antibody responses that may represent a precursor for disease. The recognition of CP(169-180) and other polypeptides provide opportunities to devise diagnostic tests for monitoring the immunological effectiveness of vaccination. Chapter 3: Porcine circovirus associated disease (PCVAD) encompasses a group of syndromes linked to infection with porcine circovirus type 2 (PCV2). Based on the hypothesis that the immune response to vaccination versus infection are quantitatively and qualitatively different, the objective of this study was to evaluate immunity, virus replication and disease protection in pigs vaccinated with PCV2 capsid protein (CP) and natural infection. The disease model included dual infection with PCV2 and porcine reproductive and respiratory syndrome virus (PRRSV), a factor known to enhance disease progression and severity. The principal effect of PRRSV infection was to increase peak PCV2 viremia by almost 40-fold; however, PCV2 failed to show a reciprocal effect on PRRSV. In vaccinated pigs, there was no evidence of disease or PCV2 replication following dual virus challenge. Immunity following vaccination favored neutralizing antibody; whereas, PCV2 infection produced high levels of non-neutralizing antibody, primarily directed against a polypeptide in the C-terminal region of CP. These results support the notion that the magnitude of the total antibody response cannot be used as a measure of protective immunity. Furthermore, protection versus disease lies in the immunodominance of specific epitopes. Epitope specificity should be taken into consideration when designing PCV2 vaccines. Chapter 4: Porcine circovirus type 2 (PCV2) capsid protein (CP) is the only protein necessary for the formation of the virion capsid and recombinant CP spontaneously forms virus-like particles (VLPs). Located within a single CP subunit is an immunodominant epitope, CP(169-180), which is exposed on the surface of the subunit; but, in the structural context of the VLP, the epitope is buried and inaccessible to antibody. High levels of anti-CP(169-180) activity are associated with porcine circovirus-associated disease (PCVAD). The purpose of this study was to investigate the role of the immune response to monomer CP in the development of PCVAD. The approach was to immunize pigs with CP monomer followed by challenge with PCV2 and porcine reproductive and respiratory syndrome virus (PRRSV). To maintain the CP immunogen as a stable monomer, CP(43-233) was fused to ubiquitin (Ub-CP). Size exclusion chromatography showed that Ub-CP was present as a single 33 kDa protein. Pigs immunized with Ub-CP developed a strong antibody response to PCV2, including antibodies against CP(169-180). However, only low levels of virus neutralizing activity were detected and viremia was similar to non-immunized pigs. As a positive control, immunization with baculovirus-expressed CP (Bac-CP) resulted in high levels of virus neutralizing activity, low amounts of anti-CP(169-180) activity, and the absence of viremia in pigs following virus challenge. The data support the role of CP(169-180) as an immunological decoy and illustrate the importance of the structural form of the CP immunogen in determining the outcome following infection.
Keywords: Porcine circovirus; Porcine circovirus associated diseasae; Epitope mapping; Decoy epitope; Antibody response